Christian Lange (ed.) - Ramelli, Ilaria (Exemplaria Classica, 2010)
Christian Lange (ed.), Ephraem der Syrer: Kommentar zum Diatessaron I. Fontes Christiani Bd. 54/1. Turnhout: Brepols, 2008, pp. 366, ISBN 9782503519746. Christian Lange (ed.), Ephraem der Syrer: Kommentar zum Diatessaron II. Fontes Christiani Bd. 54/2. Turnhout: Brepols, 2008, pp. viii + 332, ISBN 9782503528694.